2021
DOI: 10.1039/d1cp03119h
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopic characterization of the co-adsorption of CO2 and H2 onto cationic Cun+ clusters

Abstract: To understand elementary reaction steps in the hydrogenation of CO2 over copper-based catalysts, we experimentally study the adsorption of CO2 and H2 onto cationic Cun+ (n = 4–7) clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 62 publications
3
34
0
Order By: Relevance
“…We have recently reported IR multiple photon dissociation (IRMPD) spectra of Cu n + ·Ar ( n = 3–10) and of the products resulting from the individual reactions of H 2 /D 2 and CO 2 , and their combination with Cu n + . Here, we extend our work to reaction products with methane. Because Cu + binds CH 4 in η 2 coordination more strongly than Au + , it could be expected that Cu n + clusters may be more reactive toward CH 4 than Au n + clusters.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have recently reported IR multiple photon dissociation (IRMPD) spectra of Cu n + ·Ar ( n = 3–10) and of the products resulting from the individual reactions of H 2 /D 2 and CO 2 , and their combination with Cu n + . Here, we extend our work to reaction products with methane. Because Cu + binds CH 4 in η 2 coordination more strongly than Au + , it could be expected that Cu n + clusters may be more reactive toward CH 4 than Au n + clusters.…”
Section: Introductionmentioning
confidence: 83%
“…Geometries of Cu n + –CH 4 were optimized using the Gaussian 16 package with the Perdew–Burke–Ernzerhof (PBE) functional with a triple-ζ basis set with two polarization functions (Def2-TZVPP). , This functional was chosen because it has successfully explained our previous work on copper cluster cations interacting with Ar, H 2 , and CO 2 . A test calculation on the Cu 2 + –CH 4 system showed that PBE and B3LYP yield very similar predicted IR spectra. Trial geometries of the Cu n + –CH 4 complexes were constructed by taking the earlier determined structures of cationic Cu clusters and complexing them with CH 4 at several adsorption sites and configurations of CH 4 , including structures where CH 4 was dehydrogenated to form hydrido-methyl complexes.…”
Section: Methodsmentioning
confidence: 99%
“…Different types of initial cluster and bonding motifs of the H2 were investigated previously, where we performed optimization on different initial cluster geometries to locate the lowest energy bare Cu4 and Cu4 + , and different binding motifs were systematically generated using our in-house code, what has also been applied e.g in ref. [34]. The previously optimized structures with TPSSh/def2-TZVP + D3 were reoptimized using the PBE+D3/cc-pVTZ-PP (involving also relativistic effective core potential) , while single point energies were computed at the CCSD(T)/cc-pVTZ-PP, after a systematic benchmark up to CCSD(T)/def2-QZVPPD.…”
Section: Methods Of Computationsmentioning
confidence: 99%
“…In our previous work we investigated differently charged copper clusters reactions with CO2 and CO2 + H2, and we could not exclude or confirm the H2 dissociation due to the absence of characterization methods. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] To analyze elementary steps in different conditions a microkinetic model is needed. Master equation is a well-used model for combustion reaction [35], and can form a bridge between calculations and experiments, due to their validity on different pressure ranges.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been successfully used to infer the structure of cluster-molecule complexes. [67][68][69][70][71][72] For the thermal stability, we used thermal desorption spectrometry (TDS) to analyze until what temperatures cluster-NO complexes survive, from which the binding energies can be inferred.…”
Section: No Adsorption On Rhodium Clustersmentioning
confidence: 99%